Trends in hospitalization and factors associated with in‐hospital death among pediatric admissions with implantable cardioverter defibrillators. - Qasim, Amna; Dam, Tam; Kim, Jeffrey J.; Valdes, Santiago O.; Howard, Taylor; Diaz, Matthew A.; Morris, Shaine A.; Miyake, Christina Y. (Journal of Cardiovascular Electrophysiology, 2022)
Background: As pediatric implantable cardioverter‐defibrillator (ICD) utilization increases, hospital admission rates will increase. Data regarding hospitalizations among pediatric patients with ICDs are lacking. In addition, hospital mortality rates are unknown. This study aimed to evaluate (1) trends in hospitalization rates from 2000 to 2016, (2) hospital mortality, and (3) factors associated with hospital mortality among pediatric admissions with ICDs. Methods: The Kids' Inpatient Database (2000, 2003, 2006, 2009, 2012, 2016) was used to identify all hospitalizations with an existing ICD ≤20 years of age. ICD9/10 codes were used to stratify admissions by underlying diagnostic category as: (1) congenital heart disease (CHD), (2) primary arrhythmia, (3) primary cardiomyopathy, or (4) other. Trends were analyzed using linear regression. Hospital and patient characteristics among hospital deaths were compared to those surviving to discharge using mixed multivariable logistic regression, accounting for hospital clustering. Results: Of 42 570 716 hospitalizations, 4165 were admitted ≤20 years with an ICD. ICD hospitalizations increased four‐fold (p =.002) between 2000 and 2016. Hospital death occurred in 54 (1.3%). In multivariable analysis, cardiomyopathy (odds ratio [OR]: 3.5, 95% confidence interval [CI]: 1.1–11.2, p =.04) and CHD (OR: 4.8, 95% CI: 1.5–15.6, p =.01) were significantly associated with mortality. In further exploratory multivariable analysis incorporating a coexisting diagnosis of heart failure, only the presence of heart failure remained associated with mortality (OR: 8.6, 95% CI: 3.7–20.0, p <.0001). Conclusions: Pediatric ICD hospitalizations are increasing over time and hospital mortality is low (1.3%). Hospital mortality is associated with cardiomyopathy or CHD; however, the underlying driver for in‐hospital death may be heart failure.